Kesenian Sintren dalam Tarikan Tradisi dan Modernitas - Puji Dwi Darmoko (Madaniyah, 2014)
In the midst of the pressure of modernity, cultural products as a valuable culture created by the children of the nation are maintained. One of them is the regional art "Sintren" which develops along the northern coast of Central Java, especially in Pemalang Regency. Sintren's art begins with folklore / legend believed by the public about the love story of Sulasih and R. Sulandono, a son of the Mataram Regent, Joko Bahu or known by the name Bahurekso and Rr. Rantamsari. Sintren dance art is considered unique, because many say its movements are out of common sense awareness, accompanied by songs and some simple musical instruments. Along with the development of the era of sintren as an art is one of the parts of culture affected by the current of modernity. Forms of modernity, for example, places of entertainment that are modern include: cinema, café, karaoke, mall, and so on displacing the existence of art as an alternative entertainment that contains elements of education and enlightenment, especially traditional art. Sintren's art has lost its prestige, partly because the community itself does not care about Sintren's art. They assume, staging Sintren art is not relevant to the times. However, the empowerment of Sintren art still exists because of the enthusiasm of Sintren artists who strive to revive Sintren art more than a "devotion" to preserve the cultural heritage of ancestors, or want to preserve the values ​​of wisdom stored in it, as practiced by members of the Circle of Friends Sintren Slamet Rahayu Sirau Hamlet Paduraksa Village.